2015
DOI: 10.1002/adhm.201500132
|View full text |Cite
|
Sign up to set email alerts
|

Silica Microcapsules for Long‐Term, Robust, and Reliable Room Temperature RNA Preservation

Abstract: As a consequence of the latest revolutionary discoveries on its functions, RNA is certainly the hottest topic at the moment, being an exceptional tool in biology as well as in medicine. For the various applications, a proper RNA storage is required to prevent the degradation of this extremely unstable molecule. Here a novel freezing-free RNA storage strategy is presented, based on its encapsulation in silica spheres. The silica microcapsules protect the RNA by providing a water-free environment. In this way RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…As previously reported in literature, a fi rst-order nucleic acid decay kinetics was observed. [ 13,14 ] Additionally, as predicted, RNA decayed faster than DNA at all the examined temperatures ( Figure S7, Supporting Information). In Figure S8 (Supporting Information), the Δ C t is reported versus time for the various temperatures, exhibiting the expected linearity.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…As previously reported in literature, a fi rst-order nucleic acid decay kinetics was observed. [ 13,14 ] Additionally, as predicted, RNA decayed faster than DNA at all the examined temperatures ( Figure S7, Supporting Information). In Figure S8 (Supporting Information), the Δ C t is reported versus time for the various temperatures, exhibiting the expected linearity.…”
supporting
confidence: 67%
“…[ 13 ] Based on this assumption, the natural choice would be to use DNA as reference, and RNA as sensing element.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing co‐interacting reagents was a major breakthrough, which led to the various applications, including chiral optical materials . Recently, Grass and co‐workers showed that silica is a perfect environment to preserve nucleic acids for the information storage and biomedical purposes . Mirkin and co‐workers used silicification to generate stable nanoparticle superlattices, which were further converted into catalytically active materials …”
Section: Figurementioning
confidence: 99%
“…Both strategies however, have not solved the large substrate limitations. Following on previous unsuccessful attempts to directly encapsulate proteins in silica in analogy to encapsulating DNA/RNA (see supporting info), [18][19][20][21] we took advantage of literature knowledge on enzyme immobilization on mesoporous materials. To further overcome the disadvantages that immobilized enzymes have during application, we herein report a novel approach to stably entrap enzymes and release them on demand (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%